How one-year of systematic training changes the shooting performance in a group of young biathletes? - Zák, M.; Ondrácek, J.; Hrebícková, S.; Struhár, I. (Proceedings of the 11th International Conference on Kinanthropology, 2017)
Purpose: Performance of biathletes depends on many factors (for example wind speed, lighting conditions, air temperature, athlete's concentration, shooting accuracy and time and many others). The previous findings of our research proved a relationship between exercise intensity and athlete´s postural stability (centre of pressure area and anterior-posterior movement of the centre of pressure) during shooting at a standing position. Moreover, it is important to mention that not only postural balance plays a role in shooting accuracy. The objective of this paper is to evaluate a one-year progress in shooting skills of young biathletes during a systematic training. The training process of participants was mostly focused on their shooting skills, balance abilities and the development of strength-endurance abilities. Methods: Twelve healthy, well-trained biathletes (5 girls, 7 boys) volunteered to participate in the study (Girls: age 15.8 ± 0.74 years, body weight 55.20 ± 5.70 kg, body height 1.65 ± 0.03 m, VO2max 54.62 ± 3.29 ml/kgmin , Wmax/kg 4.8 ± 0.39; Boys: age 15.0 ± 0.75 years, body weight 57.42 ± 6.47 kg, body height 1.71 ± 0.07 m, VO2max 65.3 ± 2.85 ml/kgmin , Wmax/kg 4.9 ± 0.22). The centre of pressure area and anterior-posterior sway were measured by a foot pressure scan (FootWork Pro). Shooting performance and rifle stability were measured by SCATT Shooter Training System. All of these parameters were measured in rest and after a physical load (skating on roller skis) expressed by the percentage of maximum heart rate (HRmax) (5 minutes, 65-75% of HRmax; 5 minutes, 75-85% of HRmax; 5 minutes, 85-95% of HRmax). This paper presents the changes over a period of one year. Results: The stability of the rifle (the length trajectory of motion of the barrel in the last second before a shot) during the testing in rest and after a physical load was improved for all the participants. The rifle stability in the standing shooting position improved: in rest-boys (24.3%), girls (6.2%); Intensity 1 65-75% of HRmax-boys (19.5%), girls (13.9%); Intensity 2 75-85% of HRmax-boys (1.8%), girls (13.0%); Intensity 3 85-95% of HRmax-boys (16.1%), girls (17.1%). The improvement of anterior-posterior sway was found after the systematic one-year training for all biathletes. Conclusion: The results of our study showed improvement of young novice biathletes in their shooting skills. It can be assumed that the athletes' progress should continue during the next year if the same training concept is continued. To conclude, these results suggest not only progress of the biathletes but also the importance of evidence for predicting the performance in a future sport career.